Analisis Semiotika Sampul Majalah Sahabat Edisi Agustus - Oktober 2021 - Marini (Komsospol, 2021)
Sahabat Magazine is a family magazine that was formed in 2016. Sahabat Magazine is a family magazine that is packaged in an Islamic way with various complete rubrics, ranging from; The Islamic World, Figures, Communities, Entrepreneurs, Children's Work, and many others. Sahabat Magazine is one of the print media that still exists in today's digital era. In addition, Sahabat magazine also uses image illustrations in each of the presented rubrics. The composition of the rubric is also included in the cover of the magazine which makes it interesting. The Islamic messages to be conveyed are also depicted from the symbols, text meanings, and images on the cover of Sahabat magazine. This study uses a descriptive qualitative research method which is carried out by describing and analyzing the existing data. And this analysis uses Roland Barthes' Semiotics theory which discusses the meaning of denotation, connotation, and myth in the rubric found on the cover of Sahabat magazine. The analysis of this research uses the cover of Sahabat magazine Agustus – Oktober 2021 edition. The researcher concludes that the cover of Sahabat magazine is composed of denotative, connotative, and mythical markers that are related to each other and contain da'wah messages that are packaged lightly in the Islamic rubric.